Pathogenesis of brain damage in glutaric acidemia type I: Lessons from the genetic mice model. Issue 78 (21st May 2019) - Wajner, Moacir; Amaral, Alexandre Umpierrez; Leipnitz, Guilhian; Seminotti, Bianca
Abstract : Glutaric acidemia type I (GA I) is an inherited neurometabolic disease caused by deficient activity of the mitochondrial enzyme glutaryl‐CoA dehydrogenase (GCDH), resulting in predominant accumulation of glutaric and 3‐hydroxyglutaric acids derived from lysine (Lys), hydroxylysine, and tryptophan catabolism. GA I patients usually present progressive cortical leukodystrophy and frequently develop acute striatal degeneration during encephalopathic crises during the first three years of life. The pathophysiology of the neurodegeneration observed in GA I is still partly known, although the development of the genetic mice model of GA I ( Gcdh −/− ) has contributed to clarify potential underlying mechanisms involved in brain damage in this disease. In this review we will summarize the knowledge acquired from studies using this animal model indicating that disruption of redox homeostasis, glutamatergic neurotransmission and bioenergetics, as well as vascular alterations, blood‐brain barrier breakage and altered myelination underlie the cortical and striatum abnormalities and white matter changes observed in GA I patients. Elucidation of these pathomechanisms potentially offers new standpoints for the development of novel therapeutic strategies for this disease.